Prognostic significance of admission inflammatory biomarkers (CRP/albumin and ferritin) in predicting mortality and hospital stay in acute pancreatitis- A cross-sectional study. - Raj, Kisslay; Besra, Ramchandra; Bodra, Pankaj; Toppo, Samir; Sahu, Swaroop Sanat; Kujur, Anmol; Tudu, Marshal Barun; Bharati, Binit; Singh, Nalini (Student's Journal of Health Research Africa, 2025)
Background Acute pancreatitis (AP) is an inflammatory condition that can range from mild to life-threatening, commonly presenting with abdominal pain, nausea, vomiting, and elevated serum lipase or amylase. Effective management requires a comprehensive assessment, with disease severity playing a crucial role in prognosis. Objectives- This study aimed to evaluate the significance of serum ferritin and the CRP/albumin ratio in predicting the severity of AP. Materials and methods This cross-sectional study was conducted at Rajendra Institute of Medical Sciences (RIMS), Ranchi, from January 2022 to December 2022, enrolling 115 patients with acute pancreatitis. Serum levels of CRP, albumin, and ferritin were measured at admission and after 48 hours to assess their association with disease severity. Data were analyzed using SPSS version 24.0 with appropriate statistical methods. Results The mean age of participants was 45 ± 12 years, with 61% males and 39% females. The average body mass index (BMI) was 24.5 ± 3.2. The mean serum ferritin level was 350 ± 100 ng/mL, and the average CRP level was 80 ± 25 mg/L. Conclusion The study highlights that serum ferritin and the CRP/albumin ratio are useful biomarkers for assessing AP severity, showing strong correlations with disease severity and adverse outcomes. Recommendation Routine monitoring of serum ferritin and the CRP/albumin ratio is recommended for early risk assessment in patients with acute pancreatitis.